Analysis of mutations of NF1 gene in three patients with neurofibromatosis type I - LIN Yanyan; DONG Shuyan; WANG Huaiyu; LIN Lihang; XIAO Xuemin (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To detect the gene mutations in three children with neurofibromatosis type1 (NF1), and explore the new pathogenic mutations and phenotypes of NF1. [Methods] Exome sequencing and targeted gene panels were performed in the probands to determine the mutation sites. After detecting suspected mutation types in the patients, the mutation sites were verified in all patients and their parents by high-throughput sequencing and Sanger sequencing techniques. [Results] After birth, all three children (two males and one female) presented with multiple cafe-au-lait spots, axillary or inguinal freckles, and one with neurofibromas. All three patients were diagnosed with NF1, and were with a identified mutation site in the NF1 gene, i.e., c.3921delT, c.5206-2A>C and c.893T>G, respectively. The c.3921delT and c.893T>G have not been reported previously. The NF1 variation in one patient was inherited from the father, and the other two were spontaneous mutation. [Conclusion] We identify two novel mutations in NF1 gene in three children with NF1, expanding the pathogenic mutation sites of the NF1 gene.